Urban design ecologies - McGrath, Brian (AD reader, 2013)
Beskrivelse: The discipline of urban design is undergoing a rapid expansion and realignment. It is experiencing a shift from a profession dominated by architects and planners, directed at urban development, to a more expansive set of practices engaging new forms of social and environmental ecologies, as cities worldwide adapt to economic restructuring, mass migrations and climate change. Bringing together classic and new texts from the last 40 years, this AD Reader focuses attention on the critical tools needed to understand how cities have been designed and constructed and then changed over time. This enables new ways of envisioning how cities must be conceived and adapted in the future to the dual conditions of rapid urbanisation and economic restructuring, coupled with unpredictable environmental conditions due to climate change. With its emphasis on both urban design and the ecological, this book brings together key articles that point the way forward for reconciling the often conflicting concerns of urbanism and environmentalism. Twenty-three texts are organised into four distinct sections, covering metropolitan architecture, the sprawling megalopolis, the megacity and the recently emerging metacity. These are broadly chronological and highlight the recent thinking behind some of the key urban developments, ranging from the art of traditional city-making covered by European architects and historians in the late 20th century to contemporary Tokyo described by Atelier Bow-Wow. Features original texts from: Reyner Banham, Rem Koolhaas, Aldo Rossi, Colin Rowe, David Grahame Shane, Bernard Tschumi, Oswald Mathias Ungers, and Robert Venturi, Denise Scott Brown and Steven Izenour. Contains newly commissioned texts from: Mary Cadenasso, Sharon Haar and Victoria Marshall, Carlos Leite, Steward TA Pickett and Albert Pope. Includes new translations of important essays by Vittorio Gregotti and Paola Viganò. Topics range from the European historic city to the Las Vegas Strip and the megacity of São Paulo, taking in the global sustainable city.